The Contribution of Organizational Culture in Schools to Improving Teacher Performance - Adi Syaputra; Achadi Budi Santosa (Tarbawi, 2022)
The role of organizational culture in improving school quality cannot be ignored, such as hard work habits, responsibility, relationships between school members, and efforts to improve quality. Meanwhile, teacher performance is very important for academic achievement. This study aims to reveal the extent of the role of organizational culture in schools in improving teacher performance. The approach used in this study is qualitative by using the narrative literature review method. The results of this study indicate that the role of organizational culture on teacher performance is very large. However, the implementation of organizational culture faces various obstacles, such as the socialization of regulations that have not been maximized, teachers who have not been disciplined, and in general, school residents who are comfortable with their previous habits. The influence of organizational culture on teacher performance and teacher motivation is quite significant. What needs to be anticipated are the implications because organizational culture that has been embedded for a long time sometimes becomes an obstacle to the change process.